The Criteria of Passive and Low Energy in Building Design for Tropical Climate in Thailand - Nguanson, Chawadee; Taweekun, Juntakan; Dai, Yanjun; Ge, Tianshu (International Journal of Integrated Engineering, 2020)
Due to high level of energy consumption and increasing environmental concerns, energy efficiency has become a critical issue today. Buildings alone account for around 30 percent of the world’s total energy consumption. The way buildings are designed and constructed today will not only have an impact on their operating costs, but it will also affect the world’s energy consumption patterns and environmental conditions for many years to come. For much of the building industry in Thailand, the designed-in approach to energy-efficient design does not reflect current market practice. In reality, without passive design, numerous opportunitiesfor designing better performance buildings can be wasted. The integration of passive design is thus a key to energy conscious buildings. The integration of passive design approach optimizes the interactions between the natural environment, building envelope and systems as an integrated system. This research examines which components work best altogether to save energy and reduce environmental impactson buildings in the tropical region. The outcomes of this research aim to set up the criteria of passive and low energy in building design for the tropical climate in Thailand. These fundamental differences will lead to a very different architectural and constructional design. It is imperative that the decision be made at an early stage in the design and there are tremendous opportunitiesto use smart, energy efficient designs to reduce the energy footprint of the built environment for decades to come.